2014
DOI: 10.1111/1365-2664.12198
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator body size mediates the scale at which land use drives crop pollination services

Abstract: Summary1. Ecosystem services to agriculture, such as pollination, rely on natural areas adjacent to farmland to support organisms that provide services. Native insect pollinators depend on natural or semi-natural land surrounding farms for nesting and alternative foraging resources. Despite interest in conserving pollinators through habitat restoration, the scale at which land use affects pollinators and thus crop pollination services is not well understood. 2. We measured abundance of native, wild bee pollina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(93 citation statements)
references
References 46 publications
(95 reference statements)
6
76
0
4
Order By: Relevance
“…Furthermore, many different services are provided by many different organisms, even for pollination, and so, many different optimum spatial scales should be expected. These have been shown to vary with body size in wild bees (Benjamin et al 2014). The process of pollination takes place across the landscape scale.…”
Section: Assessing Competition For Spatial Use Of Landscape Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many different services are provided by many different organisms, even for pollination, and so, many different optimum spatial scales should be expected. These have been shown to vary with body size in wild bees (Benjamin et al 2014). The process of pollination takes place across the landscape scale.…”
Section: Assessing Competition For Spatial Use Of Landscape Featuresmentioning
confidence: 99%
“…This figure shows that even if each stakeholder interest seems to be independent from the other, they are indeed related through the plant-pollinator trophic network wild bee diversity, which in turn relies on semi-natural features within the landscape (Steffan-Dewenter and Westphal 2008). However, the spatial scale at which these features affect pollinator abundance and pollination function has not been fully established (Benjamin et al 2014).…”
Section: Assessing Competition For Spatial Use Of Landscape Featuresmentioning
confidence: 99%
“…Fewer rare bees were also found in these grasslands, with only 7 of the 30 rare species (i.e., those with fewer than 4 occurrences) collected. Given the large foraging ranges of honeybees and bumblebees [45] it may be surprising that lower numbers of these species are driving the association with intensive agriculture at this relatively small scale, but these findings are supported by a recent study that also found a negative response of large-bodied bees to agricultural land cover at a similar scale (300 m radius) [58].…”
Section: Discussionmentioning
confidence: 93%
“…These radii were used in order to consider a wide range of bee flight distances (Araújo et al 2004, Benjamin, Reilly & Winfree 2014. Variables at the landscape and tree levels were uncorrelated with each other.…”
Section: Landscape Metricsmentioning
confidence: 99%
“…These include works in watermelon , sweet cherry , maize (Danner et al 2014), blueberry (Benjamin et al 2014), eggplant (Gemmill-Herren & Ochieng 2008 and coffee . However, in most cases, the analysis of landscape structure was limited to few landscape features, such as the distance to forest patches (Saunders et al 2004, Rickets et al 2004, Carvalheiro et al 2010 or the amount of native habitat (Brosi et al 2008, Le Feón et al 2010.…”
Section: Introductionmentioning
confidence: 99%